Effects of the 2008–09 Economic Crisis on Labor Markets in Mexico - Freije, Samuel; López-Acevedo, Gladys; Rodríguez-Oreggia, Eduardo (2012)
The 2008-09 economic crisis has had a long-lasting negative impact on the Mexican economy. This paper examines labor market dynamics in Mexico in light of the crisis. The labor market has been characterized in recent years by low relative unemployment, but high levels of informal jobs, low-growth, and almost stagnant real wages. In this context, the crisis destroyed a wide number of formal jobs, and even informal, increasing the unemployment rates to pre-crisis levels. Manufacturing was the sector that endured the largest job losses during the crisis and wages decreased for all sectors. The government of Mexico implemented a variety of programs to cope with the crises. However, these measures were too limited to counteract the large negative impact of the crisis on labor markets.